Dietary intake and menstrual cycle changes in international level young athletes - Miyamoto, M.; Hanatani, Y.; Shibuya, K. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Few studies have examined the influence of nutritional status and mental stress on menstrual cycle characteristics. The purpose of this study was to describe the impact of low energy availability (EA) and mental health problems on the menstrual cycles of elite female rowing competitors during a survey period. METHODS: We enrolled sixteen subjects (16-18 years old) who were elite female rowing competitors preparing for an international competition. This study provides the first long-term assessment of dietary intake, body mass/composition, state of anxiety, and menstrual cycle in international level female athletes. RESULTS: Dietary energy intake increased significantly during the investigation period (P<0.001). CHO intake increased significantly during the investigation period (P<0.005). EA significantly increased during the investigation period (P<0.01). The percentage of athletes with menstrual dysfunction was 20.0% in April 2018 (2 of 10), but none of the athletes reported menstrual dysfunction in October 2019. The mental status measured by state anxiety index (STAI) did not change significantly during this survey period (P>0.05). CONCLUSIONS: There was no athlete who has menstrual disfunction after sufficient CHO intake during this survey period. These findings of this study suggest that adequate EA levels and sufficient CHO intake might lead to improved menstrual function. In addition, the impact of psychological factors on menstrual dysfunction at normal levels may be less than the effects of nutritional status.